The Relationship of Social Support and Neighborhood Perceptions among Individuals with HIV. (September 2017) - Shacham, Enbal; López, Julia D.; Önen, Nur F.; Overton, Edgar T.
Social support has been noted to improve health outcomes for individuals with HIV. Understanding how neighborhoods contribute to feelings of social support is beneficial to create environments where populations with HIV can be supported. This study assessed the relationship between neighborhood perceptions and social support with HIV management. A total of 201 individuals were recruited; individuals with HIV, 18 years or older, who were eligible to participate in the 2-hour interview. Psychiatric diagnostic interviews were conducted alongside assessments of social support and neighborhood perceptions; biomedical markers were abstracted from medical records. Correlations and linear regression analyses were performed to assess relationships between social support and neighborhood perceptions with HIV management biomarkers. The majority of the sample was male (68.8%) and African American (72.3%), with a mean age of 43.1 years. Overall, 78% were receiving combination antiretroviral therapy (cART) prescriptions, with 69% being virally suppressed. Fear of neighborhood activities was independently associated with receiving current cART. Reports of social support and neighborhood perceptions were highly correlated. Findings suggest that supportive home environments likely would improve perceptions of social support.